A comprehensive review on impact of non-thermal processing on the structural changes of food components. (November 2021) - Barbhuiya, Rahul Islam; Singha, Poonam; Singh, Sushil Kumar
Graphical abstract: Highlights: Non-thermal processing can potentially replace thermal processing technologies. Non-thermal processing alters food structure via changes in the structural components. Modification of food structure could create food products with improved and desired functionality. Undesirable odour and off-flavour due to lipid oxidation are also observed in some non-thermally treated food. Abstract: Non-thermal food processing is a viable alternative to traditional thermal processing to meet customer needs for high-quality, convenient and minimally processed foods. They are designed to eliminate elevated temperatures during processing and avoid the adverse effects of heat on food products. Numerous thermal and novel non-thermal technologies influence food structure at the micro and macroscopic levels. They affect several properties such as rheology, flavour, process stability, texture, and appearance at microscopic and macroscopic levels. This review presents existing knowledge and advances on the impact of non-thermal technologies, for instance, cold plasma treatment, irradiation, high-pressure processing, ultrasonication, pulsed light technology, high voltage electric field and pulsed electric field treatment on the structural changes of food components. An extensive review of the literature indicates that different non-thermal processing technologies can affect the food components, which significantly affects the structure of food. Applications of novel non-thermal technologies have shown considerable impact on food structure by altering protein structures via free radicals or larger or smaller molecules. Lipid oxidation is another process responsible for undesirable effects in food when treated with non-thermal techniques. Non-thermal technologies may also affect starch properties, reduce molecular weight, and change the starch granule's surface. Such modification of food structure could create novel food textures, enhance sensory properties, improve digestibility, improve water-binding ability and improve mediation of gelation processes. However, it is challenging to determine these technologies' influence on food components due to differences in their primary operation and equipment design mechanisms and different operating conditions. Hence, to get the most value from non-thermal technologies, more in-depth research about their effect on various food components is required.